PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD INPRES JAPING - Zulkifli Zulkifli; Amrah Amrah; Lutfi Lutfi (Universitas Negeri Makassar, 2023)
This study aims to describe the effect of the cooperative learning model of think talk write type on the learning outcomes of Indonesian language students at SD Inpres Japing, Patalassang District, Gowa Regency. The research approach used was quantitative with a quasi-experimental design. This research design is a non-equivalent control group design. The sample selection in this study used the probability sampling method with a simple random sampling technique. The data collection techniques used were learning outcome tests, observation sheets, and documentation. The normality test used the Kolmogorov-Smimov test with normally distributed pretest and posttest data. There is an influence on the research conducted with class V A as the experimental class and class B as the control class, as evidenced by the application of the think talk write cooperative model. The results of the application of the think talk write model at the second meeting were 73%, and at the third meeting they were 87% (very effective)